Public Relations and Local Wisdom Mining Company Strategy Through a Harmonious Approach - Martha, Zike; Ida, Rachma; Puspa, Ratih; Hakim, Lukman (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The issue of environmental damage is the hottest every time a mining company is present in the community. Starting from the issue of environmental damage to the company's arbitrary attitude toward the surrounding community. PT Nusa Alam Lestari has a way that is different from other companies, namely using a harmonious approach to local wisdom around the environment of PT Nusa Alam Lestari. In the existence of this phenomenon, researchers in this case aim to find out public relations practices and local wisdom of mining companies with a harmonious approach. The research method uses a qualitative method with a critical approach with an analysis of social construction theory. Research informants include company management, public relations practices and community leaders and local communities around the company's operational areas. PT Nusa Alam Lestari's public relations strategy uses a local wisdom approach that is instilled in the company's values ​​which have a correlation with the local community, society or traditional groups. The results of this study indicate that the analysis of social construction in PT Nusa Alam Lestari's public relations strategy includes; (1) Externalization, namely through the process of inculcating the values ​​adopted by the company that have a correlation with the community, or local customary groups. (2) The process of objectification in this case is formed from the business of PT. Nusa Alam Lestari in understanding the local community around it with the approach of local community wisdom. (3) Internalization can be implemented in the process of building a positive image for community leaders as in public relations management by frequently listening to the wishes, needs of communities, communities and traditional groups around the mine.